Efektivitas Media Video Tutorial untuk Meningkatkan Keterampilan Membuat Karupuak Jariang Bagi Disabilitas Rungu - Chania, Adilla; Budi, Setia; Zulmiyetri, Zulmiyetri; Taufan, Johandri; Handayani, Endang Sri (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this research is to examine the effectiveness of video tutorial media in enhancing the ability to make karupuak jariang. This research employs a quantitative approach with a Single Subject Research (SSR) experimental method using an A-B-A design. The study was conducted from April 11 to April 26, 2025. The subjects of this study are hearing-impaired students in the seventh grade of SLB Kemala Bhayangkari Lintau Buo. Data analysis was conducted descriptively through visual graph interpretation, with data collection techniques including observation, tests, and documentation. The research results indicate that in the first three sessions (A1), the skill level of the students remained stable at 50%. After the intervention using tutorial video media (B) for six sessions, the students' skills increased and stabilized at 92.85%. Then, in the next three sessions (A2), the students' skills showed stability at 100%. The implication of these findings is that tutorial video media has proven effective in improving the skills of making finger snacks among hearing-impaired students at SLB Kemala Bhayangkari Lintau Buo. It is recommended that tutorial video media be further improved and developed.